2012
DOI: 10.1016/j.sbspro.2012.11.397
|View full text |Cite
|
Sign up to set email alerts
|

Coaching for Learning: Exploring Coaching Psychology in Enquiry-based Learning and Development of Learning Power in Secondary Education

Abstract: Coaching psychology has been increasingly used in the discourse of education. However there has been no research systematically looking at how coaching can make difference to the knowledge construction process and learning power development in secondary students. The current study aims to understand the nature of 'coaching for learning' in terms of coaching relationships and communication between secondary school students and teachers, and to investigate how the implementation of coaching strategies in enquiry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…Aquesta estrat猫gia ha obtingut resultats positius en la promoci贸 i la millora de la salut general de les persones (Gordon-Bar, 2014; Hermens, Op den Akker, Tabak, Wijsman i Vollenbroek, 2014; Hultgren, Palmer i O' Riordan, 2013;Wang, 2012).…”
Section: Efectes Del Coachingunclassified
“…Aquesta estrat猫gia ha obtingut resultats positius en la promoci贸 i la millora de la salut general de les persones (Gordon-Bar, 2014; Hermens, Op den Akker, Tabak, Wijsman i Vollenbroek, 2014; Hultgren, Palmer i O' Riordan, 2013;Wang, 2012).…”
Section: Efectes Del Coachingunclassified
“…The new educational methodologies that are analyzed in this paper apply collective and down-up learning models and grow-up techniques from the implementation of enquirybased pedagogical strategies and tools (Wang, 2012) and gaming-based learning (Gros, 2007;Chorney, 2012;Albretch, 2012), as well as innovative methodological proposals such as those integrated in the flipped classroom (Baker, 2000, Sam and Bergman, 2014, Strayer, 2014 and coaching techniques (Wolk, 2007, Harvard Business Esentials, 2005Bandura, 1997) that are oriented, unlike classical methodologies, to promote the development and autonomous learning capacity of students.…”
Section: Introductionmentioning
confidence: 99%
“…Authors agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License transferring knowledge in form teacher-centered, with the aim of developing mind-body and analytical thinking, in order to accomplish the goal of learning achievement or students' academic performance which was not congruent with their livelihood, as well as the outside world (Wang, 2012). Whereas in present the students had to be faced with academic changes and growth of instrument for information communication and technology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the information could be accessed quickly. According to the studies of Anghel and Voicu (2013) Wang (2012) and Vogt and Rogalla (2009) found that the teacher development based on coaching and mentoring could cause the teachers and students' changing and learning, creativity, critical thinking, critical curiosity, meaningful work for children, obtaining the strategic awareness, creating one's learning relationship and resilience and obtaining the adaptive teaching competency. Consequently, the teacher development for constructing the professional teachers based on the approach of coaching and mentoring was a technique used by the teacher.…”
Section: Introductionmentioning
confidence: 99%